Fluctuating formality: homeownership, inheritance, and the official economy in urban South Africa★. (27th September 2021) - Bolt, Maxim
Abstract: One of Malinowski's legacies was a sensitivity to the ways institutions unevenly shape lives and relationships. Taking his lead, this article develops an approach to the formal economy, combining, sharpening, and extending theories of state and market infrastructures in political and economic anthropology. Focusing on urban South Africa, it examines property inheritance among the black majority previously excluded from property rights. As a lens on the formal economy, this moves beyond production to consider how social reproduction – passing on property – weaves through disjointed state processes. The article argues that the formal economy is sustained by particular performances of its scripts: different actors connect fragments of process in their own projects, with little commitment to the official logics that notionally make systems. In a setting where state responsibility over inheritance has expanded, formality's advancing frontiers throw its fluctuating character into relief: institutions' apparently coherent abstractions are given force in piecemeal fashion. Abstrait: Formalité fluctuante : propriété immobilière, héritage et économie officielle dans l'Afrique du Sud urbaine Résumé Les travaux de Malinowski nous ont rendus sensibles à la manière inégale dont les institutions modèlent les vies et les relations. À sa suite, cet article développe une approche de l'économie formelle qui combine, affûte et élargit les théories des infrastructures d'État et de marché en anthropologie politique et économique. Dans le contexte de l'Afrique du Sud urbaine, il examine la question de l'héritage de biens immobiliers au sein de la majorité noire, autrefois exclue du droit à la propriété. En se concentrant sur l'économie formelle, il va au‐delà de la production pour examiner la manière dont la reproduction sociale (la transmission de la propriété) s'insinue à travers des processus d'État disjoints. L'article fait valoir que l'économie formelle est entretenue par des interprétations particulières de ses scénarios : différents acteurs relient des fragments de processus dans leur propre projet, sans beaucoup s'intéresser à la logique officielle théoriquement à l'origine des systèmes. Dans un contexte où les responsabilités de l'État sur la transmission de l'héritage se sont élargies, l'avancement des frontières du formalisme met en évidence le caractère fluctuant de celui‐ci : les abstractions apparemment cohérentes des institutions prennent effet de manière décousue.